Cheilitis induced by systemic isotreinoin. Case Report - Mario Fonseca, Gabriel (2008)
We present a case of cheilitis induced by isotreinoin in a male subject under systemic treatment for acne. The dermatologic literature has described its oral side effects (dry mouth and cheilitis) but odontologic reports are rare even when these reactions are frequently high (95 %). Today, knowing the cosmetic treatments are supervised by dermatologists with persistent oral side effects (including after drug treatment suspension), dentists need to recognize this medical aetiology and make the appropriated actions to reduce or eliminate these affections.